PERMAINAN KONSTRUKTIF BERBASIS TUTUP BOTOL PLASTIK UNTUK MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN ANAK USIA DINI DI TAMAN KANAK-KANAK AL FIKRI BENGKULU UTARA - Nini Suryanti; Syahrul Ismet (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background of this research is the low cognitive ability of Group B children at Al Fikri Kindergarten, North Bengkulu, particularly in recognizing the concept of number symbols. This study aims to improve children's ability to recognize number symbols from 1 to 10 through the implementation of constructive play utilizing waste materials, specifically plastic bottle caps. The research method used is Classroom Action Research (CAR), adapting Kurt Lewin's model. The study was conducted in two cycles, with each cycle comprising the stages of planning, action, observation, and reflection. The subjects of this research were 14 students of Group B (8 boys and 6 girls) aged 5–6 years at Al Fikri Kindergarten in Tebat Pacur Village, North Bengkulu Regency. Data collection techniques were carried out through observations using checklist sheets, interviews, and documentation. The data were analyzed using qualitative-reflective and descriptive-quantitative methods to determine the percentage of children's classical mastery. The results showed a constant and significant increase in children's cognitive abilities in each cycle. In the initial condition (Pre-Cycle), the average percentage of classical mastery for children achieving the minimum criteria of Developing as Expected (BSH) was only 19.1%. After the constructive play intervention was implemented, the children's classical mastery increased to 42.9% in Cycle I, and jumped drastically to reach 88.1% at the end of Cycle II. This final achievement successfully exceeded the predetermined classical success indicator of ≥ 75%.